Novel role for non-homologous end joining in the formation of double minutes in methotrexate-resistant colon cancer cells. Issue 2 (23rd December 2014) - Meng, Xiangning; Qi, Xiuying; Guo, Huanhuan; Cai, Mengdi; Li, Chunxiang; Zhu, Jing; Chen, Feng; Guo, Huan; Li, Jie; Zhao, Yuzhen; Liu, Peng; Jia, Xueyuan; et al.
Abstract : Background: Gene amplification is a frequent manifestation of genomic instability that plays a role in tumour progression and development of drug resistance. It is manifested cytogenetically as extrachromosomal double minutes (DMs) or intrachromosomal homogeneously staining regions (HSRs). To better understand the molecular mechanism by which HSRs and DMs are formed and how they relate to the development of methotrexate (MTX) resistance, we used two model systems of MTX-resistant HT-29 colon cancer cell lines harbouring amplified DHFR primarily in (i) HSRs and (ii) DMs. Results: In DM-containing cells, we found increased expression of non-homologous end joining (NHEJ) proteins. Depletion or inhibition of DNA-PKcs, a key NHEJ protein, caused decreased DHFR amplification, disappearance of DMs, increased formation of micronuclei or nuclear buds, which correlated with the elimination of DHFR, and increased sensitivity to MTX. These findings indicate for the first time that NHEJ plays a specific role in DM formation, and that increased MTX sensitivity of DM-containing cells depleted of DNA-PKcs results from DHFR elimination. Conversely, in HSR-containing cells, we found no significant change in the expression of NHEJ proteins. Depletion of DNA-PKcs had no effect on DHFR amplification and resulted in only a modest increase in sensitivity to MTX. Interestingly, both DM-containing and HSR-containing cells exhibited decreased proliferation upon DNA-PKcs depletion. Conclusions: We demonstrate a novel specific role for NHEJ in the formation of DMs, but not HSRs, in MTX-resistant cells, and that NHEJ may be targeted for the treatment of MTX-resistant colon cancer.